Evaluasi Dampak Kebijakan Relokasi Pedagang Kaki Lima (PKL) di Pasar Larangan Kabupaten Sidoarjo - wakhidatul ummah (Bahasa Indonesia, 2024)
One of the trading facilities in Sidoarjo Regency is the market, whether it is a traditional, semi-modern or modern market. In accordance with Sidoarjo District Regulation No. 1/2018 on the structuring, management and empowerment of people's markets, the Sidoarjo District Government is obliged to organize, foster and empower street vendors while structuring traditional markets that are under pressure from competition with modern markets. Recently, there has been a relocation of street vendors on the west side of the Larangan Market, which is 20 meters away from the previous location and is still part of the Larangan Market. This relocation is expected to have a more positive impact than the previous condition. Based on this case, researchers are interested in examining the impact of street vendor relocation in Pasar Larangan. This study aims to describe the impact of the relocation of PKL arrangement in the Sidoarjo Regency Larangan Market. This research uses a qualitative method descriptive approach with data collection through observation, interviews, documentation. The results showed that: (1) Individual impacts have a positive effect, including sturdy stalls, appropriate parking, centralized visitor crowds, neat stall arrangements, open air circulation, and access roads that are not muddy when it rains. For buyers, parking is more organized, the market is not shabby, sellers are more organized, and the drive-thru system makes shopping more efficient. (2) The organizational impact is positive on HPP Larangan by achieving the objectives of Disperindag to improve the face of the market and the welfare of traders. (3) Community impact is positively affected by the disappearance of the unpleasant smell of garbage due to routine garbage control. (4) The impact of social institutions and systems has a positive impact with the achievement of people's market empowerment in accordance with Sidoarjo Regency Regulation No. 1/2018.